Implementasi Rangkaian Listrik Seri Dan Paralel Berdasarkan Kearifan Lokal Rumah Adat Jawa - Affandi Catur Pamungkas; Ayudia Sekar Kedaton; Didan Wakhid Nur Sakti; Rayyan Arifa; Rudi Susanto (Prosiding Seminar Nasional Teknologi Informasi dan Bisnis, 2023)
This article discusses the implementation of electrical circuits based on local wisdom applied to miniature Javanese traditional houses. Javanese traditional houses are an important part of the rich traditional culture in Indonesia. However, with the development of modern technology, aspects of traditional life such as Javanese traditional houses are often neglected. In this article, we propose the implementation of electrical circuits in miniature Javanese traditional houses based on local wisdom. This approach aims to preserve traditional cultural aspects while introducing safe and efficient electrical technology. We apply local wisdom principles, such as the use of natural materials and traditional design concepts, to integrate the electrical circuits with the aesthetic appearance of Javanese traditional houses.The article explains the main components of the electrical circuits used in miniature Javanese traditional houses, including power sources, cable installations, switches, and lighting fixtures. We also discuss safe and efficient installation methods to avoid the risks of fire or short circuits. This implementation is expected to help preserve traditional culture while providing the convenience and safety of modern electrical usage.Through this article, we propose that by combining local wisdom and modern electrical technology, miniature Javanese traditional houses can be a good representation of the unity between cultural heritage and technological innovation. This implementation can serve as an example for cultural preservation efforts in this digital era, ensuring the sustainability and safety of electrical usage.